Simulasi dan Penalaan PID pada Kapal Pengukur Volume Sedimen Menggunakan MATLAB Simulink - Christin Hutagaol; Desmira Desmira; Nur Rohima Oktiana; Muhammad Akmal Raihan; Egi Tri Saputra; Adam Falrain Wibowo (Lembaga Pengembangan Kinerja Dosen, 2026)
The research aimed to evaluate the accuracy of control system simulations using MATLAB Simulink by comparing the results with those from reference journals. This study employed simulations and comparative analysis without any hardware testing. The system model and control parameters were derived from the reference journal, and simulations were conducted to obtain the system response in the form of time-domain waveforms. The analysis focused on comparing key system response characteristics, including target point attainment speed, overshoot, and steady-state stability. The results revealed that the waveform of the simulation response closely matched the patterns observed in the reference journal, with a high degree of agreement in terms of response characteristics. MATLAB Simulink simulations were validated as a reliable tool for system response analysis, as the small differences observed did not significantly impact the overall conformity of the response characteristics. This study confirms that MATLAB Simulink is effective for validating control system performance based on reference journal simulations.